mTORC1 feedback to AKT modulates lysosomal biogenesis through MiT/TFE regulation - Kaushal Asrani; Sanjana Murali; Brandon Lam; Chan-Hyun Na; Pornima Phatak; Akshay Sood; Harsimar Kaur; Zoya Khan; Michaël Noë; Ravi K. Anchoori; C. Conover Talbot Jr.; Barbara Smith; et al. (The Journal of Clinical Investigation, 2019)
The microphthalmia family of transcription factors (MiT/TFEs) controls lysosomal biogenesis and is negatively regulated by the nutrient sensor mTORC1. However, the mechanisms by which cells with constitutive mTORC1 signaling maintain lysosomal catabolism remain to be elucidated. Using the murine epidermis as a model system, we found that epidermal Tsc1 deletion resulted in a phenotype characterized by wavy hair and curly whiskers, and was associated with increased EGFR and HER2 degradation. Unexpectedly, constitutive mTORC1 activation with Tsc1 loss increased lysosomal content via upregulated expression and activity of MiT/TFEs, whereas genetic deletion of Rheb or Rptor or prolonged pharmacologic mTORC1 inactivation had the reverse effect. This paradoxical increase in lysosomal biogenesis by mTORC1 was mediated by feedback inhibition of AKT, and a resulting suppression of AKT-induced MiT/TFE downregulation. Thus, inhibiting hyperactive AKT signaling in the context of mTORC1 loss-of-function fully restored MiT/TFE expression and activity. These data suggest that signaling feedback loops work to restrain or maintain cellular lysosomal content during chronically inhibited or constitutively active mTORC1 signaling, respectively, and reveal a mechanism by which mTORC1 regulates upstream receptor tyrosine kinase signaling.